Reducing Cross-Cultural Social Conflict through Information Services: A Guidance and Counseling Action Research Study - Nuriya Pratiwi Pane; Rosmala Dewi (Era Scientific Publisher, 2026)
Cross-cultural social conflict remains a common challenge in multicultural educational settings, particularly among adolescents who interact with peers from diverse cultural backgrounds. Limited understanding of cultural differences may lead to misunderstandings, prejudice, and social tensions that negatively affect students’ social relationships and learning environments. Therefore, effective interventions are needed to promote intercultural understanding and reduce the occurrence of cross-cultural social conflict. This study aimed to reduce cross-cultural social conflict through the implementation of information services among Grade XII KKO-PPLP students at SMAN 15 Medan. The study employed a Guidance and Counseling Action design based on the Kemmis and McTaggart model, consisting of two action cycles. The participants were 36 students enrolled in Class XII KKO-PPLP at SMAN 15 Medan. Data were collected through questionnaires, observations, interviews, and documentation. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through data reduction, categorization, and interpretation. The findings revealed a consistent reduction in cross-cultural social conflict throughout the intervention process. During the pre-cycle stage, students demonstrated moderate to high levels of conflict across several indicators, including cultural value conflicts, social norm conflicts, behavioral conflicts, conflict experiences, attitudes toward conflict, and conflict resolution efforts. Following the implementation of information services, the average conflict score decreased from 97 in the pre-cycle stage to 94 in Cycle I and further declined to 86 in Cycle II. The results also showed substantial improvements in students’ understanding of cultural diversity, tolerance toward differences, and constructive conflict resolution skills. Observational findings further indicated positive behavioral changes, including greater openness, improved interpersonal relationships, and more harmonious interactions among students from different cultural backgrounds. In conclusion, information services were found to be effective in reducing cross-cultural social conflict and promoting multicultural understanding among students. The findings highlight the importance of integrating multicultural content into school guidance and counseling programs as a strategy for fostering tolerance, social harmony, and positive intercultural relationships within diverse educational environments.